Without fear of failure. (2nd January 2021) - Beere, Jackie
Abstract : What gets in the way of 'fearless learning' is the cognitive bias that creates beliefs about our limitations and abilities. Staying true to the principle of the 'unique child' as children progress through school is a way to empower their learning and fulfilment.